Wetland Dynamic and Ecological Compensation of the Yellow River Delta based on RS. (December 2016) - Mei, HAN; Haozhe, YU
Abstract: This paper selects Landsat-5 TM remote sensing images in 2001 and 2008, field investigation, the department visits and other methods as the date source. Based on these datas, the types of the wetland, changes in wetland area and the value of wetland are obtained. And then, we estimated the loss of market value and ecological function value which caused by reduction of wetland area and the environmental pollution with the methods of market value, ecological value, cost of environmental protection investment and outcome parameters. Therefore, we made the fund allocation of wetland compensation and calculated ecological compensation standards of wetland, provided an important reference for Yellow River Delta's eco-compensation.